Composite fiber with embedded carbon nanotubes and its preparation method and application

By inserting photocatalytic nanoparticles in carbon nanotube composite fibers and annealing, the application restriction of existing photocatalytic composite materials in new functional materials is solved, and the uniform dispersion, high loading and structure of the catalyst is achieved. Stability improves photocatalytic performance and service life.

CN116272935BActive Publication Date: 2025-02-14SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310290996.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-23
Publication Date
2025-02-14
Estimated Expiration
2043-03-23

AI Technical Summary

Technical Problem

The application of existing photocatalytic composite materials in new functional materials such as smart fabrics, neural electrodes and artificial muscles is limited, due to the problems of uneven catalyst dispersion, low content, and poor structural stability of carbon nanotube fiber composite catalysts.

Method used

Using the technology of photocatalytic nanoparticles embedded in carbon nanotube composite fibers, photocatalytic nanoparticles are embedded through interpermeable pores in carbon nanotube aerogel network, and a multi-layer structure is formed through annealing treatment to achieve stable embeddedness and high catalysts. Load capacity.

Benefits of technology

The uniform dispersion of the catalyst, high loading and structural stability are achieved, the photocatalytic performance and service life are improved, and the light absorption performance and electron transmission efficiency of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116272935B_ABST
    Figure CN116272935B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite fiber of carbon nanotubes embedded with photocatalytic nanoparticles, and its preparation method and application. The composite fiber of carbon nanotubes embedded with photocatalytic nanoparticles comprises a fiber body and a functional phase; the fiber body has an interpenetrating network structure, and the interpenetrating network structure has interpenetrating pores; the functional phase comprises photocatalytic nanoparticles embedded in the interpenetrating pores; the functional phase and the network structure form a geometric structure of stacking layers. The preparation method comprises: providing a carbon nanotube precursor and an impregnation liquid, the impregnation liquid comprises a dispersant and photocatalytic nanoparticles; immersing the carbon nanotube precursor in the impregnation liquid to obtain a wet precursor; annealing the wet precursor to obtain a composite fiber of carbon nanotubes embedded with photocatalytic nanoparticles. The composite fiber of carbon nanotubes embedded with photocatalytic nanoparticles provided by the present invention has the advantages of uniform catalyst dispersion, high content, good performance stability, long service life, response to visible light, and good catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a photocatalytic nanoparticle-embedded carbon nanotube composite fiber, a preparation method and application thereof, and is particularly suitable for photocatalytic organic matter degradation reactions. Background Art

[0002] With the worsening of energy crisis and environmental pollution, the demand for developing new environmental protection technologies and materials is becoming increasingly severe. Among them, photocatalytic materials can generate photogenerated holes and photogenerated electrons under certain wavelength light conditions, and then combine with ions or molecules to generate active free radicals with oxidative or reductive properties, thereby degrading organic macromolecules into carbon dioxide or other small molecular organic matter and water. The photocatalyst itself does not change during the reaction, and has the advantages of mild conditions, simple reaction equipment, low secondary pollution, easy reaction control, easy availability of catalytic materials and low cost. Photocatalytic materials have important application potential in environmental fields such as new energy hydrogen preparation, organic degradation and sewage treatment.

[0003] At present, the most studied catalytic materials for photocatalytic reactions include titanium dioxide, zinc oxide, tin dioxide, etc. Among them, titanium dioxide has always been a hot topic in the research of photocatalysts due to its strong photocatalytic oxidation ability, non-toxicity, low cost, and simple preparation. However, due to its own shortcomings such as large band gap and high probability of recombination of photogenerated carriers, its application and promotion in daily life are seriously limited. In response to this bottleneck, people have carried out a lot of work, among which carbon-based materials represented by carbon nanotubes have become a hot topic of concern. In recent years, scientific researchers have successively carried out a lot of work on the composite of carbon nanotubes and titanium dioxide, including the development of synthesis methods and the study of activity mechanisms (Acta Physico-Chimica Sinica, 2008, 24(1): 97-102; Journal of Shihezi University: Natural Science Edition, 2014, 32(5): 583-588; Applied Catalysis B: Environmental, 2011, 110: 50-57.).

[0004] In the field of preparation of photocatalytic composite materials, a Chinese invention patent with application publication number CN 108103766 A proposes a molybdenum disulfide composite fiber photocatalyst for sewage treatment and a preparation method. The invention prepares carbon nanotube fibers by solution spinning, and performs acidification treatment under heating and ultrasonic action, and then mixes with an anhydrous methanol solution of sodium molybdate and a surfactant, passes hydrogen after natural precipitation, and heats to obtain a molybdenum disulfide composite fiber photocatalyst that can be used for sewage treatment. This method significantly improves the photocatalytic activity by firmly loading molybdenum disulfide on carbon nanotube fibers, expands the contact area between the catalyst and sewage, and effectively improves the catalytic efficiency and photocatalytic effect. In addition, the preparation method is relatively simple, with low energy consumption and low cost, and can be widely used in the fields of photocatalytic water purification, water decomposition and hydrogen production.

[0005] The Chinese invention patent with application publication number CN 103127947 A proposes a method for constructing a phosphoric acid functionalized carbon nanotube-titanium dioxide composite nano photocatalyst. The invention prepares phosphoric acid functionalized carbon nanotubes, then adds the phosphoric acid functionalized carbon nanotubes to butyl titanate to obtain an organic phase, and further grinds and mixes to obtain a product, and uses phosphoric acid to functionalize the carbon nanotubes, thereby improving the oxygen adsorption capacity of the carbon nanotubes and enhancing the ability of the carbon nanotubes in the composite system to promote the separation and reaction of photogenerated carriers.

[0006] The Chinese invention patent with application publication number CN 101777431 A proposes a method for preparing a thin film electrode of titanium dioxide-coated carbon nanotubes. Compared with the prior art, the method for preparing a thin film electrode of titanium dioxide-coated carbon nanotubes of the invention has the following advantages: since carbon nanotubes are a one-dimensional material with good electrical conductivity and chemical stability, after introducing them into the traditional P25 particle thin film electrode, the conduction efficiency of photoelectrons in the film can be improved, the transmission resistance of electrons in the film can be reduced, and the short-circuit current can be effectively increased, thereby ultimately achieving the purpose of increasing the photoelectric conversion efficiency of dye-sensitized solar cells.

[0007] The Chinese invention patent with authorization announcement number CN100396373C proposes a method for preparing a carbon nanotube-modified titanium dioxide composite photocatalyst. The invention provides a method that does not destroy the carbon nanotubes. The carbon nanotubes and titanium dioxide are strongly combined and have a high efficiency in photocatalytic decomposition of water to produce hydrogen. The modification of the carbon nanotubes enables the catalyst to have the ability to absorb visible light, greatly improving the light utilization rate of the titanium dioxide photocatalyst.

[0008] However, existing research results have focused on the simple composite of carbon nanotube powder and catalytic component nanoparticles such as titanium dioxide, which is not conducive to further weaving and application in new functional materials such as smart fabrics, neural electrodes and artificial muscles. Although there have been a small number of studies on fiber composite catalyst nanoparticles, they are all based on simple fiber molding followed by surface growth, coating or carbon nanotube composite and then further spinning molding, which belongs to the micron-level composite. The carbon nanotube fiber composite catalyst particles prepared by the above schemes have problems such as low content, poor structural stability caused by easy detachment of catalytic particles, difficulty in penetration of catalyst particles into the interior of carbon nanotube fibers, unsatisfactory catalytic efficiency, and difficulty in controlling carbon nanotube orientation, gaps and the interface between catalyst and carbon tubes. Summary of the invention

[0009] In view of the deficiencies of the prior art, the object of the present invention is to provide a composite fiber of photocatalytic nanoparticles embedded with carbon nanotubes, and a preparation method and application thereof.

[0010] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0011] In a first aspect, the present invention provides a photocatalytic nanoparticle-embedded carbon nanotube composite fiber, which comprises a fiber body and a functional phase dispersed in the fiber body;

[0012] The fiber body has an interpenetrating network structure formed by the interpenetration of carbon nanotubes, and the interpenetrating network structure has interpenetrating pores and forms a complex fold morphology;

[0013] The functional phase includes photocatalytic nanoparticles, which are embedded in the interpenetrating pores and combined with the wrinkles of the fiber body to form a multilayer structure.

[0014] In a second aspect, the present invention further provides a method for preparing a composite fiber of photocatalytic nanoparticles embedded with carbon nanotubes, comprising:

[0015] Providing a carbon nanotube precursor and an impregnation liquid, wherein the carbon nanotube precursor is an aerogel-like substance formed by the aggregation of carbon nanotubes, and the impregnation liquid comprises a dispersant and photocatalytic nanoparticles dispersed in the impregnation liquid;

[0016] Immersing the carbon nanotube precursor in the impregnation liquid to obtain a wet precursor;

[0017] The wet precursor is subjected to annealing treatment to obtain composite fibers containing photocatalytic nanoparticles and embedded carbon nanotubes.

[0018] In a third aspect, the present invention also provides the use of the above-mentioned photocatalytic nanoparticle-embedded carbon nanotube composite fiber in the field of photocatalytic hydrogen preparation or photocatalytic organic matter degradation.

[0019] In a fourth aspect, the present invention further provides a method for photocatalytic degradation of organic matter, comprising:

[0020] Providing the above-mentioned photocatalytic nanoparticle-embedded carbon nanotube composite fiber;

[0021] The photocatalytic nanoparticles embedded in the carbon nanotube composite fiber are brought into contact with the organic matter to be degraded and oxygen to form a degradation reaction system, and light is applied to the degradation reaction system to photocatalytically degrade the organic matter to be degraded.

[0022] Based on the above technical solution, compared with the prior art, the beneficial effects of the present invention at least include:

[0023] ① The catalyst is evenly dispersed and has a high content. Since there are a large number of uniform interpenetrating voids in the carbon nanotube aerogel network, it is conducive to the attachment of catalyst nanoparticles that are affinity to carbon nanotubes after modification, and form uniform embedding in the aerogel network; in addition, unlike the arbitrary dispersion of carbon nanotube networks and organic solvents caused by organic impregnation liquids, and unlike the agglomeration and shrinkage of carbon nanotubes caused by pure water impregnation liquids, this method optimizes the dispersion system, controls the shrinkage of hydrophobic carbon nanotube precursors under the action of dispersants to form complex wrinkles, and uses surface-treated nanoparticles to form a layered composite structure of carbon nanotube networks. The capillary channels generated by the wrinkles and multi-layer structure can absorb the nanoparticle dispersion into the grooves and interior of the carbon nanotube fiber network under the action of capillary force, achieving stable embedding and high loading of photocatalytic nanoparticles. Compared with the disclosed carbon nanotube aerogels directly immersed in modified solutions, this method has adjustable internal fiber structure and good electron transmission capacity of carbon nanotube network sheets.

[0024] ②Good stable performance and long service life. Due to the large number of continuous interpenetrating network structures in carbon nanotube fibers, the photocatalytic nanoparticles can not only form a weak force bond with the carbon tubes, but also form a tight to loose coating structure from the surface to the inside under different tensions and linear speed differences due to the aerogel-like carbon nanotube precursor during the contraction process, which effectively mechanically fixes the photocatalytic nanoparticles and is beneficial to improving the service life of the photocatalytic material.

[0025] ③Good catalytic performance. The catalytic particles are evenly dispersed and have a high loading capacity. In addition, due to the reorientation and re-adjustment of the interpenetrating network of carbon nanotube aerogels during continuous compounding, shrinkage and annealing, the structure and stress optimization of the interface between carbon tubes in the fiber and between nanoparticles and fibers are achieved, which is conducive to the efficient transmission of electrons during photocatalytic applications. From the results of the UV-visible diffuse reflectance spectrum tested on the fiber material, it was found that there was a synergistic effect between carbon nanotubes and photocatalytic nanoparticles, which effectively improved the light absorption performance of the material and reduced the band gap by 0.59 eV, making the material have effective absorption capacity for visible light, able to generate more photogenerated carriers, and maximize the catalytic efficiency.

[0026] The above description is only an overview of the technical solution of the present invention. In order to enable those skilled in the art to more clearly understand the technical means of the present application and implement them according to the contents of the specification, the following is a description of the preferred embodiments of the present invention in conjunction with detailed drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a scanning electron microscope (SEM) photograph of a photocatalytic nanoparticle-embedded carbon nanotube composite fiber in a knotted state provided by a typical implementation case of the present invention;

[0028] Figure 2a This is a low-magnification cross-sectional SEM photograph of a composite fiber of photocatalytic nanoparticles embedded with carbon nanotubes provided in a typical embodiment of the present invention;

[0029] Figure 2b This is a high-magnification cross-sectional SEM photograph of a composite fiber with embedded carbon nanotubes and photocatalytic nanoparticles provided in a typical embodiment of the present invention;

[0030] Figure 3a This is a low-magnification side SEM photograph of a composite fiber with embedded carbon nanotubes and photocatalytic nanoparticles provided in a typical embodiment of the present invention;

[0031] Figure 3b This is a high-magnification side SEM photograph of a composite fiber with embedded carbon nanotubes and photocatalytic nanoparticles provided in a typical embodiment of the present invention;

[0032] Figure 4a This is a comparison diagram of the light absorption characteristics of a photocatalytic nanoparticle-embedded carbon nanotube composite fiber and pure titanium dioxide provided in a typical implementation case of the present invention;

[0033] Figure 4b This is a comparison diagram of the band gap size changes of a photocatalytic nanoparticle-embedded carbon nanotube composite fiber and pure titanium dioxide provided in a typical implementation case of the present invention;

[0034] Figure 5This is a test diagram of the cyclic degradation efficiency of methylene blue solution by a photocatalytic nanoparticle-embedded carbon nanotube composite fiber provided in a typical implementation case of the present invention;

[0035] Figure 6 This is a test chart of the degradation efficiency of methylene blue solution of titanium dioxide nanoparticles and their embedded carbon nanotube composite fibers provided in a typical implementation case of the present invention. DETAILED DESCRIPTION

[0036] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The purpose of the present invention is to overcome the deficiencies of the prior art and provide a high-performance photocatalytic nanoparticle-embedded carbon nanotube composite fiber for photocatalysis and a preparation method thereof. The technical solution, its implementation process and principle, etc. will be further explained as follows.

[0037] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0038] See also Figure 1 , Figure 2a and Figure 2b as well as Figure 3a and Figure 3b An embodiment of the present invention provides a photocatalytic nanoparticle-embedded carbon nanotube composite fiber, which includes a fiber body and a functional phase dispersed in the fiber body.

[0039] The fiber body has an interpenetrating network structure formed by the interpenetration of carbon nanotubes, and the interpenetrating network structure has interpenetrating pores.

[0040] The functional phase includes photocatalytic nanoparticles and carbon nanotubes. The photocatalytic nanoparticles are embedded in the interpenetrating pores, combined with the wrinkles of the fiber body to form a multilayer structure, and have a synergistic effect with the carbon nanotubes.

[0041] In the above technical solution, if you want to form a multilayer structure with photocatalytic nanoparticles prepared by water dispersant, such as titanium dioxide nanoparticles, in carbon nanotubes, you can only do it before the carbon nanotube aerogel network shrinks. Finally, the embedded multilayer structure shown in the figure was successfully prepared.

[0042] In some embodiments, the carbon nanotube has a diameter of 5-15 nm and an aspect ratio of more than 1000:1.

[0043] In some embodiments, the photocatalytic nanoparticles, especially titanium dioxide nanoparticles, have a particle size of 20-150 nm.

[0044] In some embodiments, the titanium dioxide nanoparticles have a mixed anatase and rutile crystal structure.

[0045] In some embodiments, the mass fraction of titanium dioxide nanoparticles in the photocatalytic nanoparticle-embedded carbon nanotube composite fibers is 65-85%.

[0046] As some typical application examples of the above technical scheme, a high-performance photocatalytic nanoparticle-embedded carbon nanotube composite fiber for photocatalysis is exemplified in an embodiment of the present invention, comprising a highly oriented carbon nanotube fiber main body accounting for 15-35% by mass and a titanium dioxide nanoparticle functional phase with a particle size of 20-150nm accounting for 65-85% by mass; the highly oriented carbon nanotube fiber main body has a continuous interpenetrating network structure, and the interpenetrating network structure is formed by carbon nanotubes with a large aspect ratio of 5-15nm in diameter that are entangled and overlapped with each other, and a highly oriented structure is naturally formed under the tension and stretching action during the preparation process; the titanium dioxide nanoparticle functional phase is embedded in the gap of the interpenetrating network structure of the high-oriented carbon nanotube fiber main body to form a mechanically tight anchoring, and the titanium dioxide nanoparticle functional phase can preferably be a mixed crystal structure of anatase and rutile.

[0047] The linear density of the composite fiber can be 150-200 dtex, and the specific surface area can be 60-100 m 2 / g, tensile strength at break is 100-200MPa, elongation at break is 4-10%, and conductivity can be 500-1200S / cm. However, it is not limited to this, and the density, strength and elongation of the fiber depend on the specific fiber preparation process.

[0048] Corresponding to the above composite fiber, an embodiment of the present invention also provides a method for preparing a composite fiber of photocatalytic nanoparticles embedded with carbon nanotubes, which comprises the following steps:

[0049] A carbon nanotube precursor and an impregnation liquid are provided. The carbon nanotube precursor is an aerogel-like substance formed by the aggregation of carbon nanotubes. The impregnation liquid comprises a dispersant and photocatalytic nanoparticles dispersed in the impregnation liquid.

[0050] The carbon nanotube precursor is immersed in the impregnation liquid to obtain a wet precursor.

[0051] The wet precursor is subjected to annealing treatment to obtain composite fibers containing photocatalytic nanoparticles and embedded carbon nanotubes.

[0052] In some very typical implementation cases, firstly, a carbon nanotube aerogel network is continuously prepared based on floating catalytic chemical vapor deposition technology (FCCVD). Since there are a large number of uniform interpenetrating voids in the carbon nanotube aerogel network, it is conducive to the uniform embedding of titanium dioxide catalyst nanoparticles in the aerogel network. In addition, by modifying the surface of titanium dioxide nanoparticles and optimizing the reasonable dispersion system, the shrinkage degree of hydrophobic carbon nanotubes under capillary action is controlled, and the nano titanium dioxide dispersion is absorbed into the surface grooves and the interior of the carbon nanotube fiber, so as to achieve a high loading amount of titanium dioxide. Further, since the main body of the carbon nanotube fiber is formed by the continuous entanglement of a large number of carbon nanotube fibers with a high aspect ratio, a large number of continuous interpenetrating network structures are formed in the entire fiber, and the titanium dioxide nanoparticles can not only form a weak force combination with the carbon tube, but also form a tight to loose coating structure from the surface to the inside due to the different tensions and linear speed differences of the carbon nanotube aerogel sleeve during the contraction process, forming an effective mechanical fixation of a large number of titanium dioxide nanoparticles in the fiber, which is conducive to improving the service life of the material. Finally, since tension is continuously applied to the interpenetrating network of carbon nanotube aerogel during the continuous compounding, shrinking and drying processes, it is beneficial to the structural readjustment of the highly oriented structure of the carbon nanotubes and the connected pore network, and is beneficial to the structural and stress optimization of the interfaces between carbon nanotubes in the fibers and between nanoparticles and fibers. It is also beneficial for the efficient transmission of electrons generated by titanium dioxide in the catalytic process with the help of the high carrier mobility characteristics of oriented carbon nanotubes, thereby maximizing the catalytic efficiency.

[0053] In some embodiments, the carbon nanotube precursor is prepared by a floating catalytic chemical vapor deposition method.

[0054] In some embodiments, the dispersant includes any one or a combination of two or more of methanol, ethanol, acetonitrile, water, etc., and is not limited thereto.

[0055] In some embodiments, the method for preparing the impregnation solution comprises:

[0056] Titanate and a complexing agent are mixed and then subjected to complexing reaction to obtain a titanium dioxide precursor; the titanium dioxide precursor is surface-modified by a surfactant; the surface-modified titanium dioxide precursor and an acid catalyst are prepared into a liquid phase reaction system, aged for 10-48 hours, and then dried to obtain a powder; the powder is heat-treated at 250-450° C. for 1-3 hours to obtain titanium dioxide nanoparticles; the titanium dioxide nanoparticles are dispersed in the dispersant to obtain the dispersion.

[0057] In some embodiments, the photocatalytic nanoparticles are first dispersed in an organic dispersant, and after partial volatilization, water is added to the organic dispersant to form a composite dispersion system.

[0058] In some embodiments, the titanate includes any one of tetrabutyl titanate and titanium isopropoxide, or a combination of both, but is not limited thereto.

[0059] In some embodiments, the complexing agent includes any one of glacial acetic acid and acetylacetone or a combination of both, but is not limited thereto.

[0060] In some embodiments, the acid catalyst includes any one of nitric acid and sulfuric acid or a combination of both, but is not limited thereto.

[0061] In some embodiments, the annealing treatment is performed at a temperature of 400-800° C. and for a time of 1-3 h.

[0062] In some embodiments, the annealing process is performed in a protective atmosphere.

[0063] In some embodiments, the cylindrical carbon nanotube precursor is continuously introduced into the impregnation solution, and the formed linear wet precursor is continuously rolled up.

[0064] As some typical application examples of the above technical solution, a method for preparing high-performance photocatalytic nanoparticle-embedded carbon nanotube composite fibers for photocatalysis adopts the following specific steps to implement the above technical solution:

[0065] (1) Continuously prepare carbon nanotube aerogel network based on floating catalytic chemical vapor deposition technology (FCCVD): a carbon source, a catalyst and a promoter are introduced into a high-temperature vertical reactor, and the temperature of the reaction zone is controlled at 1200-1450°C to form a continuous carbon nanotube aerogel network as the carbon nanotube precursor. As for how to prepare aerogel-state carbon nanotube precursors, a large number of technical solutions have been disclosed in the prior art, which are mature options and will not be repeated here.

[0066] (2) Preparation of titanium dioxide nanoparticle impregnation solution: 20-30 parts of tetrabutyl titanate are added to 80-120 parts of anhydrous ethanol and stirred vigorously. 4-10 parts of glacial acetic acid are slowly added dropwise as a complexing agent and mixed evenly. Stirring is continued for 10-30 minutes to obtain a homogeneous light yellow solution, which is cooled in an ice water bath for later use, and is recorded as solution A. Then 8-12 parts of distilled water, 0.5-2 parts of concentrated nitric acid, and 50-70 parts of anhydrous ethanol are uniformly mixed, and an appropriate amount of surfactant (including but not limited to polyethylene glycol, PVP, PVA, sodium oleate, etc.) is added. An appropriate amount of concentrated nitric acid is slowly added dropwise to adjust the solution pH to 2-5, and stirred for 10-30 minutes, which is recorded as solution B. Solution B is added to the vigorously stirred solution A at a rate of 10-30 drops per minute, and then the solution is allowed to stand for 4-9 hours to obtain a light yellow gel; finally, the above solution is allowed to stand for aging in a ventilated place for 10-48 hours, dried at 50-80°C, ground and annealed at 250-450°C under a protective atmosphere for 1-3 hours to obtain nano-scale titanium dioxide powder. The nanopowder is washed three times with deionized water and ethanol, acetonitrile is added for ultrasonic dispersion, the acetonitrile is volatilized and deionized water is added, and finally a titanium dioxide nanoparticle impregnation solution is obtained.

[0067] (3) Directly introducing the carbon nanotube aerogel network prepared in step (1) into the titanium dioxide nanoparticle impregnation solution prepared in step (2), and continuously compounding, winding and rolling in an inert gas-encapsulated environment to form wet fibers of carbon nanotube composite fibers embedded with photocatalytic nanoparticles.

[0068] (4) After unwinding the wet fiber of the photocatalytic nanoparticle-embedded carbon nanotube composite fiber prepared in step (3), the wound monofilament is placed in a CVD furnace at 400-800°C for constant temperature annealing for 1-3h (heating rate 10°C / min) under a nitrogen atmosphere to obtain a high-performance, long-life photocatalytic nanoparticle-embedded carbon nanotube composite fiber that can be used for photocatalysis.

[0069] The above process exemplifies a process of continuous winding followed by annealing. However, considering that the floating vapor deposition method can continuously produce fibers, the above process can also be prepared in a continuous production line.

[0070] As an application example corresponding to the above technical solution, an embodiment of the present invention also provides the application of the above photocatalytic nanoparticle-embedded carbon nanotube composite fiber or the fiber prepared by the above method in the field of photocatalytic hydrogen preparation or photocatalytic organic matter degradation.

[0071] Some specific examples of the above application are a method for photocatalytic degradation of organic matter provided by an embodiment of the present invention, which comprises the following steps:

[0072] Provide the above-mentioned photocatalytic nanoparticle embedded carbon nanotube composite fiber or the fiber prepared by the above-mentioned method.

[0073] The photocatalytic nanoparticles embedded in the carbon nanotube composite fiber are brought into contact with the organic matter to be degraded and oxygen to form a degradation reaction system, and light is applied to the degradation reaction system to photocatalytically degrade the organic matter to be degraded.

[0074] The technical solution of the present invention is further described in detail below through several embodiments and in conjunction with the accompanying drawings. However, the selected embodiments are only used to illustrate the present invention, and do not limit the scope of the present invention.

[0075] Example 1

[0076] This embodiment illustrates a high-performance titanium dioxide nanoparticle-embedded carbon nanotube composite fiber for photocatalysis, including a high-oriented carbon nanotube fiber main body accounting for 35% by weight and a titanium dioxide nanoparticle functional phase with a particle size of 20 nm accounting for 65% by weight; the high-oriented carbon nanotube fiber main body has a continuous interpenetrating network structure, and the interpenetrating network structure is formed by carbon nanotubes with a large aspect ratio and an average tube diameter of 10 nm, which are entangled and overlapped with each other, and form a high-oriented structure under the action of multi-stage tension stretching; the titanium dioxide nanoparticle functional phase is embedded in the gap of the interpenetrating network structure of the high-oriented carbon nanotube fiber main body to form a mechanically tight anchoring, and the titanium dioxide nanoparticle functional phase is a mixed crystal structure of anatase and rutile.

[0077] The composite fiber has a density of 150 dtex and a specific surface area of ​​70 m 2 / g, tensile strength is 200MPa, and elongation at break is 10%.

[0078] In addition, this embodiment also illustrates a method for preparing the above-mentioned high-performance, long-life photocatalytic nanoparticle-embedded carbon nanotube composite fiber for photocatalysis, comprising the following steps:

[0079] (1) Continuous preparation of carbon nanotube aerogel network based on floating chemical vapor deposition technology (FCCVD): The carbon source, catalyst and promoter are introduced into a high-temperature vertical reactor, and the temperature of the reaction zone is controlled at 1200°C to form a continuous carbon nanotube aerogel network.

[0080] (2) Preparation of titanium dioxide nanoparticle impregnation solution: 20 parts of tetrabutyl titanate were added to 80 parts of anhydrous ethanol and stirred vigorously. 5 parts of glacial acetic acid were slowly added as a complexing agent and mixed evenly. Stirring was continued for 10-30 minutes to obtain a homogeneous light yellow solution, which was cooled in an ice water bath for later use, and recorded as solution A. Then 9 parts of distilled water, 1 part of concentrated nitric acid, and 50 parts of anhydrous ethanol were uniformly mixed, and an appropriate amount of surfactant (including but not limited to polyethylene glycol, PVP, PVA, sodium oleate, etc., sodium oleate was used in this embodiment) was added, and an appropriate amount of concentrated nitric acid was slowly added to adjust the pH of the solution to 2, and stirred for 10 minutes, and recorded as solution B. Solution B was added to the vigorously stirred solution A at a rate of 10 drops per minute, and the solution was then allowed to stand for 9 hours to obtain a light yellow gel; finally, the above solution was allowed to stand for 48 hours in a ventilated place, dried at 80°C, ground, and annealed at 400°C in a protective atmosphere for 2 hours to obtain nano-scale titanium dioxide powder. The nanopowder was washed three times with deionized water and ethanol, and acetonitrile was added as a dispersant for ultrasonic dispersion. The acetonitrile was volatilized and added with deionized water to finally obtain a titanium dioxide nanoparticle impregnation solution.

[0081] (3) The carbon nanotube aerogel network prepared in step (1) is directly introduced into the titanium dioxide nanoparticle impregnation solution prepared in step (2), and continuously compounded, wound and rolled in an inert gas-encapsulated environment to form titanium dioxide nanoparticle-embedded carbon nanotube composite fiber wet fibers.

[0082] (4) After unwinding the wet fiber of titanium dioxide nanoparticle embedded carbon nanotube composite fiber prepared in step (3), the wound single fiber is annealed at a constant temperature of 400°C in a CVD furnace for 3 hours (heating rate of 10°C / min) under a nitrogen atmosphere to obtain high-performance and long-life titanium dioxide nanoparticle embedded carbon nanotube composite fiber that can be used for photocatalysis.

[0083] The macroscopic morphology of the composite fiber prepared in this embodiment is as follows: Figure 1 As shown, due to the interpenetrating network composed of carbon nanotubes with a high aspect ratio, even after compounding a large amount of inorganic functional phases, the fiber can still maintain its flexibility and toughness and is not easily damaged after being knotted.

[0084] The cross section of the fiber obtained in this embodiment was observed under an electron microscope, and the photographs thereof at different magnifications are as follows: Figure 2a and Figure 2b As shown, it can be seen that while the carbon nanotubes are interpenetrating, they have a significant tendency to be oriented along the axial direction of the fiber as a whole, and the titanium dioxide nanoparticles are completely coated by the oriented and interpenetrating structure formed by the carbon nanotubes, and can achieve a relatively uniform and tight composite inside and outside, forming a new composite structure that is completely different from the skin-core or short carbon nanotube and nanoparticle stray composite in the prior art.

[0085] Regarding the surface of the fiber, its electron microscopic morphology is as follows Figure 3a and Figure 3b As shown, especially from the high magnification Figure 3b An obvious orientation + interpenetrating structure can be seen in the figure. In addition, the spherical titanium dioxide nanoparticles are not agglomerated, but are well dispersed and tightly surrounded and fixed by the network formed by carbon nanotubes. Such a structure not only plays a role in mechanical fixation, but also can use the conductive network formed by carbon nanotubes to significantly improve the transmission efficiency of electrons and maximize the catalytic efficiency.

[0086] This example also conducted UV-visible diffuse reflectance spectroscopy tests on the composite fiber and the pure titanium dioxide obtained in the above steps. The results are as follows: Figure 4a and Figure 4b As shown, after compounding, the absorption spectrum of titanium dioxide, especially the wavelength corresponding to the absorption peak, has undergone very obvious changes, indicating that the band gap size of the composite material has changed. This shows that the carbon nanotube network in the fiber not only plays a role in mechanical fixation, but also can interact with titanium dioxide. This change should be an important influencing factor in obtaining better catalytic efficiency.

[0087] Example 2

[0088] This embodiment illustrates a high-performance titanium dioxide nanoparticle-embedded carbon nanotube composite fiber for photocatalysis, including a high-oriented carbon nanotube fiber main body accounting for 15% by weight and a titanium dioxide nanoparticle functional phase with a particle size of 150 nm accounting for 85% by weight; the high-oriented carbon nanotube fiber main body has a continuous interpenetrating network structure, and the interpenetrating network structure is formed by carbon nanotubes with a large aspect ratio and an average tube diameter of 15 nm, which are entangled and overlapped with each other, and form a high-oriented structure under the action of multi-stage tension stretching; the titanium dioxide nanoparticle functional phase is embedded in the gap of the interpenetrating network structure of the high-oriented carbon nanotube fiber main body to form a mechanically tight anchoring, and the titanium dioxide nanoparticle functional phase is a mixed crystal structure of anatase and rutile.

[0089] The composite fiber has a density of 200 dtex and a specific surface area of ​​60 m 2 / g, tensile strength is 100MPa, and elongation at break is 4%.

[0090] In addition, this embodiment also illustrates a method for preparing the above-mentioned high-performance and long-life titanium dioxide nanoparticle-embedded carbon nanotube composite fiber for photocatalysis, comprising the following steps:

[0091] (1) Continuous preparation of carbon nanotube aerogel network based on floating chemical vapor deposition technology (FCCVD): The carbon source, catalyst and promoter are introduced into a high-temperature vertical reactor, and the temperature of the reaction zone is controlled at 1450°C to form a continuous carbon nanotube aerogel network.

[0092] (2) Preparation of titanium dioxide nanoparticle impregnation solution: 20 parts of tetrabutyl titanate were added to 80 parts of anhydrous ethanol and stirred vigorously. 5 parts of glacial acetic acid were slowly added as a complexing agent and mixed evenly. Stirring was continued for 10-30 minutes to obtain a homogeneous light yellow solution, which was cooled in an ice water bath for later use, and recorded as solution A. Then 9 parts of distilled water, 1 part of concentrated nitric acid, and 50 parts of anhydrous ethanol were uniformly mixed, and an appropriate amount of surfactant (including but not limited to polyethylene glycol, PVP, PVA, sodium oleate, etc., PVP was used in this embodiment) was added, and an appropriate amount of concentrated nitric acid was slowly added to adjust the pH of the solution to 2, and stirred for 10 minutes, and recorded as solution B. Solution B was added to the vigorously stirred solution A at a rate of 10 drops per minute, and the solution was then allowed to stand for 9 hours to obtain a light yellow gel; finally, the above solution was allowed to stand for 48 hours in a ventilated place, dried at 80°C, ground, and annealed at 400°C in a protective atmosphere for 2 hours to obtain nano-scale titanium dioxide powder. The nanopowder was washed three times with deionized water and ethanol, and acetonitrile was added as a dispersant for ultrasonic dispersion. The acetonitrile was volatilized and added with deionized water to finally obtain a titanium dioxide nanoparticle impregnation solution.

[0093] (3) The carbon nanotube aerogel network prepared in step (1) is directly introduced into the titanium dioxide nanoparticle impregnation solution prepared in step (2), and continuously compounded, wound and rolled in an inert gas-encapsulated environment to form titanium dioxide nanoparticle-embedded carbon nanotube composite fiber wet fibers.

[0094] (4) After unwinding the wet fiber of the titanium dioxide nanoparticle embedded carbon nanotube composite fiber prepared in step (3), the wound single fiber is annealed at a constant temperature of 800°C in a CVD furnace for 1 h (heating rate of 10°C / min) under a nitrogen atmosphere to obtain a high-performance, long-life titanium dioxide nanoparticle embedded carbon nanotube composite fiber that can be used for photocatalysis.

[0095] Example 3

[0096] This embodiment illustrates a high-performance titanium dioxide nanoparticle-embedded carbon nanotube composite fiber for photocatalysis, including a high-oriented carbon nanotube fiber main body accounting for 20% by weight and a titanium dioxide nanoparticle functional phase with a particle size of 100 nm accounting for 80% by weight; the high-oriented carbon nanotube fiber main body has a continuous interpenetrating network structure, and the interpenetrating network structure is formed by carbon nanotubes with a large aspect ratio and an average tube diameter of 10 nm, which are entangled and overlapped with each other, and form a high-oriented structure under the action of multi-stage tension stretching; the titanium dioxide nanoparticle functional phase is embedded in the gap of the interpenetrating network structure of the high-oriented carbon nanotube fiber main body to form a mechanically tight anchoring, and the titanium dioxide nanoparticle functional phase is a mixed crystal structure of anatase and rutile.

[0097] The composite fiber has a density of 180 dtex and a specific surface area of ​​80 m 2 / g, tensile strength is 150MPa, and elongation at break is 7%.

[0098] In addition, this embodiment also illustrates a method for preparing a high-performance, long-life titanium dioxide nanoparticle-embedded carbon nanotube composite fiber for photocatalysis, comprising the following steps:

[0099] (1) Continuous preparation of carbon nanotube aerogel network based on floating chemical vapor deposition technology (FCCVD): The carbon source, catalyst and promoter are introduced into a high-temperature vertical reactor, and the temperature of the reaction zone is controlled at 1350°C to form a continuous carbon nanotube aerogel network.

[0100] (2) Preparation of titanium dioxide nanoparticle impregnation solution: 20 parts of tetrabutyl titanate were added to 80 parts of anhydrous ethanol and stirred vigorously. 5 parts of glacial acetic acid were slowly added as a complexing agent and mixed evenly. Stirring was continued for 10-30 minutes to obtain a homogeneous light yellow solution, which was cooled in an ice water bath for later use, and recorded as solution A. Then 9 parts of distilled water, 1 part of concentrated nitric acid, and 50 parts of anhydrous ethanol were uniformly mixed, and an appropriate amount of surfactant (including but not limited to polyethylene glycol, PVP, PVA, sodium oleate, etc., polyethylene glycol was used in this embodiment) was added, and an appropriate amount of concentrated nitric acid was slowly added to adjust the pH of the solution to 2, and stirred for 10 minutes, and recorded as solution B. Solution B was added to the vigorously stirred solution A at a rate of 10 drops per minute, and then the solution was allowed to stand for 9 hours to obtain a light yellow gel; finally, the above solution was allowed to stand for 48 hours in a ventilated place, dried at 80°C, ground, and annealed at 400°C in a protective atmosphere for 2 hours to obtain nano-scale titanium dioxide powder. The nanopowder was washed three times with deionized water and ethanol, and acetonitrile was added as a dispersant for ultrasonic dispersion. The acetonitrile was volatilized and added with deionized water to finally obtain a titanium dioxide nanoparticle impregnation solution.

[0101] (3) The carbon nanotube aerogel network prepared in step (1) is directly introduced into the titanium dioxide nanoparticle impregnation solution prepared in step (2), and continuously compounded, wound and rolled in an inert gas-encapsulated environment to form titanium dioxide nanoparticle-embedded carbon nanotube composite fiber wet fibers.

[0102] (4) After unwinding the wet fiber of the titanium dioxide nanoparticle embedded carbon nanotube composite fiber prepared in step (3), the wound single fiber is annealed at a constant temperature of 600°C in a CVD furnace for 2h (heating rate 10°C / min) under a nitrogen atmosphere to obtain a high-performance, long-life titanium dioxide nanoparticle embedded carbon nanotube composite fiber that can be used for photocatalysis.

[0103] Example 4

[0104] This embodiment illustrates a photocatalytic application of a composite fiber with titanium dioxide nanoparticles embedded in carbon nanotubes, as shown below:

[0105] A 20 mg / L methylene blue aqueous solution was used as the solution to be degraded, into which the photocatalytic nanoparticles embedded carbon nanotube composite fibers prepared in Example 2 were added at a feed ratio of 1 g / L, and then a teaching xenon lamp was used as the light source (light intensity of 100 mW / cm 2 ) 50 mL of the target solution was irradiated to achieve photocatalytic degradation.

[0106] After the primary degradation is completed, the photocatalytic nanoparticle-embedded carbon nanotube composite fiber is taken out, washed and dried, and then put into the degradable liquid of the same concentration and volume according to the same feed ratio for cyclic photocatalytic degradation.

[0107] 5 times of photocatalytic degradation efficiency test Figure 5 As shown, it can be seen that although the degradation efficiency decays during multiple degradations, the residual rate of methylene blue in the solution remains below 10% after 2 hours of degradation.

[0108] Comparative Example 1

[0109] This comparative example illustrates an application example of pure titanium dioxide nanoparticles for photocatalytic degradation, as shown below:

[0110] The titanium dioxide nanoparticles prepared in step (2) of Example 2 were subjected to the same photocatalytic degradation experiment as in Example 4 at the same feed ratio.

[0111] like Figure 6 As shown, with the same 2-hour photocatalytic degradation time, in the first cycle, the residual rate of methylene blue was 31.6%, which was significantly higher than that of Example 4. However, due to the use of nanoparticle powder, the recovery loss was extremely large and the conditions for recycling were not met.

[0112] Comparative Example 2

[0113] This comparative example illustrates an application example of the photocatalytic degradation of the carbon nanotube-titanium dioxide composite material in the prior art, as shown below:

[0114] Preparation process of composite materials: titanium isopropoxide (TTIP) and glacial acetic acid (GAA) were mixed and stirred at room temperature for 10 minutes, which was recorded as solution A. 20 mg of sodium dodecyl sulfate (SDS) was dissolved in 10 mL of deionized water and stirred at room temperature for 15 minutes, which was recorded as solution B. Solution B was added to solution A and stirred for 30 minutes to prepare TTIP-GAA-SDS gel. 4 mL of hydrochloric acid was diluted to 40 mL with deionized water, and then slowly added to the TTIP-GAA-SDS gel to gradually obtain a transparent solution, and then 0.5 mg of carbon nanotubes (CNTs) were added and stirred at room temperature for 15 minutes. The solution was then transferred to a Teflon reactor for hydrothermal reaction at 150°C for 6 hours. After the reaction, it was washed with deionized water several times, and then dried at 60-100°C for 1-3 hours. After obtaining the dry powder, it was placed in a CVD furnace and annealed at 400°C for 4 hours to obtain CNT-TiO 2 Composite materials.

[0115] The same photocatalytic degradation experiment as in Example 4 was carried out using the above carbon nanotube-titanium dioxide composite material at the same feed ratio.

[0116] With the same 2-hour photocatalytic time, in the first cycle, the residual rate of methylene blue was 40%; in the third cycle, the residual rate had risen to 48%, with an obvious decay trend.

[0117] Comparative Example 3

[0118] This comparative example illustrates an application example of photocatalytic degradation of carbon nanotube composite fibers embedded with photocatalytic nanoparticles, as shown below:

[0119] The preparation of the composite material is substantially the same as that of Example 2, except that step (2) of preparing titanium dioxide nanoparticles and their dispersion by catalytic method is omitted, and instead titanium dioxide nanoparticles prepared by commercial ball milling method are dispersed in the same dispersant as the impregnation liquid.

[0120] The same photocatalytic degradation experiment as in Example 4 was carried out using the above carbon nanotube-titanium dioxide composite material at the same feed ratio.

[0121] With the same 2-hour photocatalytic time, the residual rate of methylene blue was 30% in the first cycle; in the fifth cycle, the residual rate was stabilized at 30%.

[0122] This comparative example illustrates that in the technical solution of the present invention, the use of a specific preparation method to modify the surface of the formed titanium dioxide is a key factor in achieving a higher catalytic effect and cycle performance.

[0123] Comparative Example 4

[0124] This comparative example illustrates an application example of photocatalytic degradation of carbon nanotube composite fibers embedded with photocatalytic nanoparticles, as shown below:

[0125] The preparation of the composite material is substantially the same as that of Example 2, except that step (4) of high temperature annealing of the wet fibers is omitted and low temperature drying is used instead, at 150-200° C. until there is no more weight loss.

[0126] The same photocatalytic degradation experiment as in Example 4 was carried out using the above carbon nanotube-titanium dioxide composite material at the same feed ratio.

[0127] With the same photocatalytic time of 2 hours, in the first cycle, the residual rate of methylene blue was 35.3%. Due to the failure of high-temperature annealing to stabilize the material structure and change the titanium dioxide crystal form, the degradation effect was much lower than that of Example 4. In addition, since the illumination area and the contact area with the solution of the nanoparticles were reduced compared with each other, the degradation effect was not as good as that of Comparative Example 1.

[0128] This comparative example shows that in the technical solution of the present invention, it is necessary not only to fully wrap and contain the titanium dioxide nanoparticles by the carbon nanotube network, but also to cooperate with a specific high-temperature treatment process to generate interaction between the interfaces, which is also a key factor in achieving excellent catalytic performance.

[0129] In addition, the present invention also replaces the titanium dioxide nanoparticles with other nanoparticles with photocatalytic properties, and adopts a similar method to modify the surface of the titanium dioxide nanoparticles with surfactants and cooperate with corresponding dispersants and composite methods, as well as subsequent high-temperature annealing treatment methods, and can still obtain composite fibers with excellent photocatalytic degradation properties.

[0130] Based on the above embodiments and comparative examples, it can be clearly seen that the photocatalytic nanoparticle-embedded carbon nanotube composite fiber provided in the embodiments of the present invention has the following advantages:

[0131] ① The catalyst is evenly dispersed and has a high content. The large number of uniform interpenetrating voids in the carbon nanotube aerogel network is conducive to the uniform embedding of titanium dioxide catalyst nanoparticles in the aerogel network; in addition, through the surface modification of titanium dioxide nanoparticles and the selection of a reasonable organic dispersion system, the hydrophobic carbon nanotube precursor is controlled to shrink under the action of the dispersant to form complex folds, and the nano-titanium dioxide dispersion is absorbed into the surface grooves and interior of the carbon nanotube fiber, achieving a high loading amount of titanium dioxide nanoparticles.

[0132] ②Good stable performance and long service life. Due to the large number of continuous interpenetrating network structures in carbon nanotube fibers, titanium dioxide nanoparticles can not only form a weak force bond with carbon tubes, but also form a tight to loose coating structure from the surface to the inside under different tensions and linear speed differences during the contraction process of the aerogel-like carbon nanotube precursor, which effectively mechanically fixes the titanium dioxide aerogel, which is beneficial to improve the service life of the photocatalytic material.

[0133] ③Good catalytic performance. The catalytic particles are evenly dispersed and have a high loading capacity. In addition, due to the reorientation and re-adjustment of the interpenetrating network of carbon nanotube aerogels during continuous compounding, shrinkage and annealing, the structure and stress optimization of the interface between carbon tubes in the fiber and between nanoparticles and fibers is achieved, which is conducive to the efficient transmission of electrons in the photocatalytic application process and maximizes the catalytic efficiency.

[0134] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite fiber of photocatalytic nanoparticles embedded with carbon nanotubes, characterized in that: include: A carbon nanotube precursor and an impregnation liquid are provided, wherein the carbon nanotube precursor is prepared by a floating catalytic chemical vapor deposition method and is an aerogel-like substance formed by the aggregation of carbon nanotubes, and the impregnation liquid comprises a dispersant and photocatalytic nanoparticles dispersed in the impregnation liquid; The carbon nanotube precursor is immersed in the impregnation liquid to obtain a wet precursor, wherein the carbon nanotube precursor shrinks under the action of the dispersant to form complex folds, and the carbon nanotube network is layered with the help of nanoparticles to obtain a layered composite structure, and the capillaries generated by the folds and the multilayer structure absorb the photocatalytic nanoparticle dispersion into the grooves and interior of the carbon nanotube fiber network under the action of capillary force; Annealing the wet precursor to obtain a composite fiber with photocatalytic nanoparticles embedded in carbon nanotubes, wherein the photocatalytic nanoparticles are combined with the wrinkles of the fiber body to form a multilayer structure; Wherein, the photocatalytic nanoparticles are selected from titanium dioxide nanoparticles, and the preparation method of the impregnation solution comprises: The titanate and the complexing agent are mixed and then subjected to complexing reaction to obtain a titanium dioxide precursor; Using a surfactant to perform surface modification treatment on the titanium dioxide precursor; The surface-modified titanium dioxide precursor and an acid catalyst are prepared into a liquid phase reaction system, aged for 10-48 hours, and then dried to obtain a powder, and the powder is heat-treated at 250-450° C. for 1-3 hours to obtain titanium dioxide nanoparticles; The titanium dioxide nanoparticles are dispersed in the dispersant to obtain the dispersion.

2. The preparation method according to claim 1, characterized in that The dispersant includes any one of methanol, ethanol, acetonitrile and water or a combination of two or more thereof.

3. The preparation method according to claim 1, characterized in that: The photocatalytic nanoparticles are first dispersed in an organic dispersant, and then water is added to the organic dispersant.

4. The preparation method according to claim 1, characterized in that: The titanate includes any one of tetrabutyl titanate and titanium isopropoxide or a combination of the two; The complexing agent includes any one of glacial acetic acid and acetylacetone or a combination of the two; The acid catalyst includes any one of nitric acid and sulfuric acid or a combination of the two.

5. The preparation method according to claim 1, characterized in that: The annealing treatment is performed at a temperature of 400-800°C and for a time of 1-3 h.

6. The preparation method according to claim 5, characterized in that: The annealing treatment is performed in a protective atmosphere.

7. The preparation method according to claim 5, characterized in that: The cylindrical carbon nanotube precursor is continuously put into the impregnation liquid, and the formed linear wet precursor is continuously rolled up.

8. The photocatalytic nanoparticle-embedded carbon nanotube composite fiber obtained by the preparation method according to any one of claims 1 to 7, characterized in that: It includes a fiber main body and a functional phase dispersed in the fiber main body; The fiber body has an interpenetrating network structure formed by the interpenetration of carbon nanotubes, and the interpenetrating network structure has interpenetrating pores and forms a complex fold morphology; The functional phase comprises photocatalytic nanoparticles, which are selected from titanium dioxide nanoparticles and have a mixed crystal structure of anatase and rutile. The photocatalytic nanoparticles are embedded in the interpenetrating pores and combined with the wrinkles of the fiber body to form a multilayer structure.

9. The photocatalytic nanoparticle-embedded carbon nanotube composite fiber according to claim 8, characterized in that: The carbon nanotubes have a diameter of 5-15 nm and an aspect ratio of more than 1000:1; The particle size of the photocatalytic nanoparticles is 20-150 nm.

10. The photocatalytic nanoparticle-embedded carbon nanotube composite fiber according to claim 8, characterized in that: The mass fraction of titanium dioxide nanoparticles in the photocatalytic nanoparticle-embedded carbon nanotube composite fiber is 65-85%.

11. Use of the composite fiber of photocatalytic nanoparticles embedded with carbon nanotubes as claimed in any one of claims 8 to 10 in the field of photocatalytic hydrogen production or photocatalytic organic matter degradation.

12. A method for photocatalytic degradation of organic matter, characterized in that: include: Providing a photocatalytic nanoparticle-embedded carbon nanotube composite fiber as described in any one of claims 8 to 10; The photocatalytic nanoparticles embedded in the carbon nanotube composite fiber are brought into contact with the organic matter to be degraded and oxygen to form a degradation reaction system, and light is applied to the degradation reaction system to photocatalytically degrade the organic matter to be degraded.

Citation Information

Patent Citations

  • Method for preparing carbon nanometer tube / titanium dioxide composite photocatalyst

    CN100396373C

  • Method for preparing carbon nanotube film electrode coated by titanium dioxide

    CN101777431A

  • Construction method of phosphoric acid functionalized carbon nanometer pipe-titanium dioxide composite nanometer photocatalyst

    CN103127947A

  • Molybdenum disulfide composite fiber photocatalyst for sewage treatment and preparation method thereof

    CN108103766A

  • Photocatalyst / carbon nanotube aerogel composites

    US20180229219A1